Bedside reduction of gastroschisis: A preliminary experience in yaounde-cameroon - Faustin Felicien Mouafo Tambo; Gaelle Therese Badjang; Gacelle Fossi Kamga; Salihou Aminou Sadjo; Irene Nadine Kouna Tsala; Gervais Andze Ondobo; Maurice Aurélien Sosso (African Journal of Paediatric Surgery, 2023)
Background: Gastroschisis denotes a congenital or sporadic malformation of the anterior abdominal wall, which is rarely associated with other anomalies. The mortality in African countries is still high almost 100%. Objective: The aim was to determine the feasibility and safety of bedside reduction of gastroschisis and factors affecting the outcome in low-income setting. Methodology: This was a retrospective, descriptive and analytic study over a period of 6 years conducted in the Pediatric Surgery Service of the Yaoundé Gyneco-Obstetric and Pediatric Hospital. Only neonates with gastroschisis seen within 6 h of life without bowel necrosis and in whom bedside reduction was attempted in the neonatology unit under sedation (with 0.5 mg/kg of diazepam intra-rectally and 0.5–1 mg of atropine intravenously) were included in this study. Ethical clearance was obtained for the Ethical Committee of the Yaoundé Gyneco-Obstetric and Pediatric Hospital and a signed consent form was required from the parents of the children prior to the procedure. Results: Twelve neonates with a mean age of 16.8 h (0 and 24 h) and mean birth weight of 2245 g (1860–3600 g) were enrolled. The mean time to presentation at hospital was 3.5 h (2–9 h). Bedside closure was successful in 10 patients. Two patients underwent primary closure in the theatre after failure of bedside reduction due to the volume of contents of gastroschisis. Mortality rate in our study was 33.3% and the morbidity was dominated by compartment syndrome and malnutrition. Conclusion: Bedside reduction of gastroschisis under sedation in Yaoundé seems to be way to reduce the mortality.